Enhanced ethanol production from tree trimmings via microbial consortium pretreatment with selective degradation of lignin. (November 2020) - Lin, Yunqin; Zheng, Haomin; Dong, Liang
Abstract: The microbial consortia designedly screened in our lab were used for solid-state pretreatment of tree trimmings to degrade lignin selectively in this work, and the commercial fungal isolate pretreatment was taken in comparison. The results showed that a highly selective degradation of lignin was observed in the tree trimmings pretreated via the microbial consortium DM-1, in which 14.0% of lignin was decomposed and no significant degradation of cellulose was noted within 20 days. Meanwhile, in this trial, shorter fibers and a lower crude fiber crystallinity were found in the tree trimmings after pretreatment. And the pH values of the tree trimmings undergoing biopretreatment in each trial were all kept at around 7.0. In the SSF (simultaneous saccharification and fermentation) process, 20% increment of the ethanol yield was obtained in the trial loaded with DM-1 pretreated tree trimmings compared to the control, in which a higher acid-based buffering capability was also observed. The scanning electron microscope test revealed that after SSF, the DM-1 pretreated tree trimmings had less crude fibers and more void ratios. Herein, it was feasible to produce more ethanol from tree trimmings via solid-state pretreatment by using the microbial consortium DM-1. Graphical abstract: Image 1 Highlights: Highly selective degradation of lignin was observed in solid-state pretreatment with microbial consortium DM. No contamination was noted in trials culturing in an aseptic environment within 15 days. 20% increment of ethanol yield was obtained in the reactor loaded with DM pretreated tree trimmings. No pH adjustment was required in the processes of pretreatment and SSF, respectively.